Penerapan Pidana Mati dalam Perspektif Undang - Undang No. 1 Tahun 2023 Tentang Kuhp Nasional - Adbaida Adbaida; Engrina Fauzi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Law No. 1 of 2023 concerning the National Criminal Code, in Article 100 regulates the death penalty with a 10-year probationary period which has given rise to much debate and problems. In this article 100, there has been a shift in the paradigm of the death penalty from a principal punishment to a special punishment. This will open up a gap in legal uncertainty and the potential for transactional practices in assessing "good behavior" in prisons. The formulation of the problem discussed is How is the Regulation of the application of the death penalty in the National Criminal Code, and What is the Mechanism for the application of the death penalty in Law No. 1 of 2023 concerning the National Criminal Code. The research method used is normative juridical with a statute approach, a conceptual approach, and a comparative approach. The results of the study show that in the National Criminal Code, the death penalty no longer occupies a position as a principal punishment but is repositioned as a special punishment that is alternative or as a last resort (ultimum remedium). The implementation mechanism introduces innovation in the form of a 10-year probationary period which must be included in the judge's decision. If the convict demonstrates commendable behavior and conducts during the probationary period and shows remorse, the death penalty can be commuted to life imprisonment through a Presidential Decree after consideration by the Supreme Court. However, this study also highlights concerns regarding the potential for abuse of power, transactional practices, and intervention by the judicial mafia in the evaluation process at correctional institutions during the probationary period. Therefore, strict and transparent derivative regulations are needed to maintain the dignity of justice for victims and the integrity of the national legal system. This study concludes that the death penalty in Law No. 1 of 2023 remains a legitimate instrument of retributive justice to protect the rule of law and the right to life of victims of extraordinary crimes. Although Article 100 introduces a 10-year probationary period, this mechanism should be viewed as a strict filter and not a legal loophole that weakens the ultimate deterrent effect. Therefore, derivative regulations of the National Criminal Code must ensure that the evaluation process for convicts is carried out in a rigid, transparent, and objective manner to maintain the dignity of justice for society.